Effects of Liquid-Gas Fraction on Vibrational Behaviour of Piping System - Hazarudin, Nurul ‘Awatif Hanani (IRC, 2020)
The two-phase flow of gas and liquids are normally found inside the oil and gas industry. The differences in properties and fractions of a two-phase flow mixture might cause vibration due to the variation of flow momentum. Excessive vibrations in piping systems might affect the safety of the plant and the integrity of the piping system. This phenomenon happens due to the excitation force that may exist by the different density and void fraction of gas inside the two-phase flow. This project presents a study on the vibration issue of the piping system due to the slug flow, which will be focusing on the effect of different liquid-gas void fraction onto the horizontal and vertical piping orientation and 90 elbow piping system. A set of six trials of three different void fractions and flow rate of 100 l/min and 200 l/min were used in this experiment. Analysis was done on the flow behavior at tee-junction and elbows to fully understand the causes and effects that it might have on the piping system. It is found that as there is a slight effect of increasing void fraction into the piping vibration.